La adquisición fónica de un grupo de estudiantes de primer año de las carreras de Bachillerato en Francés y en la Enseñanza del Francés de la UCR durante el primer semestre de 2010 - Castro Esquivel, Laura (2013)
This article presents the preliminary results of the research project entitled “The Phonic Acquisition by a Group of First-Year Majors of the B.A. programs in French and French Teaching at the University of Costa Rica during the first semester of 2010”. The study consists of the analysis of the informants’ first recording of oral production. Such recordings are aimed at enlightening the stages of phonic acquisition that students get  through while taking the course LM-2111 Integrated French I in order to propose some accompanying strategies to make this process more effective.